Efektivitas Program 3P (Peel, Prepare, Protect) untuk Meningkatkan Pengetahuan Duta Generasi Berencana Kota Bukittinggi Tahun 2023 Mengenai Perilaku Seks Pranikah - Rina Syafri Yani; Nurul Amanda; Salmaa Khairiyah; Siti Raudhatul Jannah; Adinda Nur Annisa Jannah; Maya Yasmin (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: Premarital sexual behavior is very common in adolescents and young adults. Their lack of knowledge is one of the causes of this happening. The negative consequences caused by this premarital sexual behavior make various prevention efforts necessary. As an effort towards this, the researchers launched the 3P (Peal, Prepare, Protect) program for Duta Generasi Berencana Kota Bukittinggi 2023. The reason to choose Duta Generasi Berencana (GenRe) as a participant is because they are icons and role models for adolescents, and later they can provide insights to adolescents about premarital sex behavior as part of their duties. Methods: The method in this service is to provide psychoeducation as a workshop about premarital sexual behavior. The analysis in the study was carried out by comparing the data before and after the intervention. Results: The result of this program showed that there was an increase in knowledge of Duta Genre Bukittinggi 2023 based on the result of a statistical test (sig. 0,000). Conclusion: In order to increase knowledge about premarital sexual behavior and to raise awareness of the negative consequences, the 3P program has been done for Duta Generasi Berencana Kota Bukittinggi 2023. It is hoped that this program will continue to be implemented so that it can be as effective as possible in preventing cases of premarital sex.